Decoding the Type 2 Diabetes Epidemic in Rural India. Issue 2 (17th February 2017) - Little, Matthew; Humphries, Sally; Patel, Kirit; Dewey, Cate
ABSTRACT: Type 2 diabetes mellitus is an escalating public health problem in India, associated with genetic susceptibility, dietary shift, and rapid lifestyle changes. Historically a disease of the urban elite, quantitative studies have recently confirmed rising prevalence rates among marginalized populations in rural India. To analyze the role of cultural and sociopolitical factors in diabetes onset and management, we employed in-depth interviews and focus groups within a rural community of Tamil Nadu. The objectives of the study were to understand sources and extent of health knowledge, diabetes explanatory models, and the impact of illness on individual, social, and familial roles. Several cultural, socioeconomic, and political factors appear to contribute to diabetes in rural regions of India, highlighting the need to address structural inequities and empower individuals to pursue health and well-being on their own terms.